2006
DOI: 10.1152/ajprenal.00219.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ERK1/2 pathway mediates oxidant-induced decreases in mitochondrial function in renal cells

Abstract: Previously, we showed that oxidant exposure in renal proximal tubular cells (RPTC) induces mitochondrial dysfunction mediated by PKC-epsilon. This study examined the role of ERK1/2 in mitochondrial dysfunction induced by oxidant injury and whether PKC-epsilon mediates its effects on mitochondrial function through the Raf-MEK1/2-ERK1/2 pathway. Sublethal injury produced by tert-butylhydroperoxide (TBHP) resulted in three- to fivefold increase in phosphorylation of ERK1/2 and p38 but not JNK. This was followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 52 publications
5
88
0
1
Order By: Relevance
“…However, ERK1/2 appears to regulate mitochondrial functions differently in various cell types, and the differences may be based on the level of oxidative phosphorylation that occurs in each cell type. RPTC used by Nowak et al (7) and in our studies derive all their energy from oxidative phosphorylation, similar to that found in kidney cortex.…”
Section: Erk1/2 Regulates Pgc-1␣supporting
confidence: 86%
See 2 more Smart Citations
“…However, ERK1/2 appears to regulate mitochondrial functions differently in various cell types, and the differences may be based on the level of oxidative phosphorylation that occurs in each cell type. RPTC used by Nowak et al (7) and in our studies derive all their energy from oxidative phosphorylation, similar to that found in kidney cortex.…”
Section: Erk1/2 Regulates Pgc-1␣supporting
confidence: 86%
“…In a study utilizing H 2 O 2 injury in human renal cells, ERK1/2 inhibition was shown to decrease necrosis and apoptosis (5), whereas in a cisplatin-induced cell injury model, ERK1/2 inhibition reduced caspase 3 activation and apoptosis (6). In renal proximal tubular cells (RPTC), phosphorylated ERK1/2 was shown to reduce mitochondrial respiration and ATP production by decreasing complex I electron transport chain activity in response to tert-butyl hydroperoxide (TBHP), a model oxidant (7). Nowak et al (7) also showed that expression of a constitutively active MEK1 increased ERK1/2 activation and decreased basal and uncoupled oxygen consumption, a measure of electron transport chain activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were grown to confluence and harvested for isolation of mitochondrial and cytosolic fractions as previously described [20].…”
Section: Cellular Fractionationmentioning
confidence: 99%
“…These results are consistent with reports from other laboratories where ERK activation lies downstream of mitochondrially-induced ROS [76][77][78][79], although , these studies did not examine ERK activation within mitochondria. Nowak et al have suggested that mitochondrially activated ERK suppresses mitochondrial respiration in oxidatively damaged tert-butylhydroperoxide treated renal epithelial cells [80]. Interestingly, while decreased mitochondrial respiration and ATP production were reversed by inhibition of the MEK/ERK pathway, these inhibitors did not restore mitochondrial aconitase activity [80].As mitochondrial aconitase inactivation is a sensitive indicator for mitochondrial superoxide, activation of the MEK/ERK pathway in this study was downstream of mitochondrial oxidative stress, but upstream of other aspects of mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%